2017
DOI: 10.4049/jimmunol.1601482
|View full text |Cite
|
Sign up to set email alerts
|

Immune Modifications in Fetal Membranes Overlying the Cervix Precede Parturition in Humans

Abstract: In humans, parturition is currently viewed as an intrauterine outbreak of inflammation, accompanied by a massive release of proinflammatory cytokines at the maternal-fetal interface that comprises the maternal decidua, placenta, and fetal membranes. At term, fetal membranes overlying the cervix, the future site of rupture, show altered morphology and are termed the zone of altered morphology (ZAM). These alterations occur in normal fetal membranes during late pregnancy, in preparation for labor. In this study,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
36
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 47 publications
3
36
0
2
Order By: Relevance
“…In addition, the membrane immune pathway also participates in the onset of labor . Innate immune cells mediate the activation of labor by releasing proinflammatory cytokines .…”
Section: Introductionsupporting
confidence: 82%
“…In addition, the membrane immune pathway also participates in the onset of labor . Innate immune cells mediate the activation of labor by releasing proinflammatory cytokines .…”
Section: Introductionsupporting
confidence: 82%
“…This perspective needs to be expanded to understand phenotypic activities by macrophages and other immune cells of lymphoid lineage in the cervix. Moreover, the time course of critical cellular and biomolecular processes in fetal membranes of the so-called zone of altered morphology that overlays the internal os of the cervix (176), as well as within the internal fetal-maternal interface must be integrated to develop a unified mechanism for parturition. Hypotheses generated and tested in various animal models described in this review would help identify the chronology of relevant biomarkers for translational studies and with clinical relevance.…”
Section: Discussionmentioning
confidence: 99%
“…14 Clinical and animal (mainly mouse) studies have identified key roles of specific cytokines, chemokines and immune cell types in the parturition process. 515 Endocrine signals arising from the fetus, such as corticotropin-releasing hormone and adrenocorticotropic hormone, are postulated to function as a biologic clock translating organ maturation and triggering labor at term. These hormones are known to have pro-inflammatory effects on various tissues in vitro.…”
Section: Introductionmentioning
confidence: 99%